Capital Flows and the Swiss Franc - Pınar Yeşin (Swiss Journal of Economics and Statistics, 2017)
The Swiss franc is known to appreciate strongly during financial market turmoil, demonstrating its status as a typical safe haven currency. One possible mechanism behind this appreciation during times of global turmoil is assumed to be higher capital inflows to Switzerland. This paper attempts to find some empirical evidence for this presumption. The analysis reveals that capital flow variables are not necessarily coincident with the movements of the Swiss franc. Interest rate differentials, a traditional determinant of exchange rates, co-move only weakly with Swiss franc movements. However, a robust and stronger link between variables that capture global or regional market uncertainty and movements of the Swiss franc is observed. Specifically, the information channel rather than new cross-border investment is found to be coincident with the Swiss franc. The weak link between capital flows and the exchange rate is confirmed to some extent for some other countries.
Keywords: F21; F31; F32; 330; Exchange rate; safe haven currency; gross capital flows; net flows; private flows